A unique investigation of thallium, tellurium, osmium, and other heavy metals in recurrent pregnancy loss: A novel approach. Issue 3 (20th August 2022) - Tabassum, Hajera; Alrashed, May; Malik, Abdul; Alanazi, Samyah T.; Alenzi, Naif D.; Ali, Mir Naiman; AlJaser, Feda S.; Altoum, Ghadah H.; Hijazy, Sereen M.; Alfadhli, Reem A.; Alrashoudi, Reem; Akhtar, Suhail
Abstract: Objective: To study the impact of heavy metals especially tellurium, thallium, and osmium, in recurrent pregnancy loss (RPL) and to study their association with antioxidant status and DNA damage. Methods: This case–control study included women with RPL ( n  = 30) and healthy pregnant women as control ( n  = 30). Following blood collection, serum levels of thallium, tellurium, osmium, lead, mercury, and cadmium were estimated by inductively coupled plasma mass spectrophotometer. Results: Women with RPL exhibited significantly higher levels of heavy metals (P  < 0.001) when compared with control women. Intriguingly, increased levels of serum thallium, tellurium, osmium, and lead were negatively correlated with total antioxidant status ( P  < 0.05). Further, the RPL group demonstrated strong positive correlation between heavy metals (thallium, tellurium, osmium, lead) and DNA damage ( P  < 0.05). No significant correlation between other heavy metals and markers of cellular damage was noted. Conclusion: Enhanced levels of heavy metals in women with RPL and correlation of thallium, tellurium, osmium, and lead with markers of cellular damage reflect the role of heavy metal poisoning, especially thallium, tellurium, and osmium, as potential risk factor in the etiology underlying recurrent miscarriage. Synopsis: Higher levels of thallium, tellurium, and osmium and subsequent cellular damage are indicative of heavy metal poisoning as potential risk factor underlying recurrent pregnancy loss.